I'm having some trouble finding a recursive definition for the following sequence:

$x_0 = \sqrt{1+n}$

$x_1 = \sqrt{1+n\sqrt{1+(n+1)}}$

$x_2 = \sqrt{1+n\sqrt{1+(n+1)\sqrt{1+(n+2)}}}$

$x_3 = \sqrt{1+n\sqrt{1+(n+1)\sqrt{1+(n+2)\sqrt{1+(n+3)}}}}$

and so on (where $n \in \mathbb{N}$). I tried using something like $x_{i+1} = \sqrt{1 + n f(x_i)}$ where $f$ would be a function that sends $n$ to $n+1$ wherever $n$ appears in $x_i$. So for instance $f(x_0) = \sqrt{1 + (n+1)}$ and $f(x_1) = \sqrt{1+(n+1)\sqrt{1+(n+2)}}$. My problem is that I can't figure out an explicit form for $f$. If it's any help, the limit of the sequence is $n+1$.


One has $x_k(n) = f_{k+1}(n)$, where $(f_k)_{k \geqslant 0}$ is the sequence of functions defined recursively as follows:

$f_0(n) = 1$

$f_{k+1}(n) = \sqrt{1+nf_k(n+1)}$


$f_0(n) = 1$

$f_1(n) = \sqrt{1+n}$

$f_2(n) = \sqrt{1+n\sqrt{1+(n+1)}}$

$f_3(n) = \sqrt{1+n\sqrt{1+(n+1)\sqrt{1+(n+2)}}}$


| cite | improve this answer | |

Recall that a sequence $(x_k)$ can be defined recursively if there exists some function $g$ such that $x_{k+1}=g(x_k)$ for every $k$.

Of course, every given strictly increasing sequence, such as the sequences considered in the question, can be defined recursively, using any function $g$ defined on $X=\{x_k\mid k\geqslant0\}$ by $g(x_k)=x_{k+1}$ and, say, by $g(x)=0$ for every $x\notin X$.

This version of the question is rather shallow since every sequence $(x_k)$ can be defined recursively in this sense except if there exists $k<\ell$ such that $x_k=x_\ell$ and $x_{k+1}\ne x_{\ell+1}$, which never happens for strictly monotonous sequences.

A more interesting version would be to ask whether all the sequences $(x_k)$ in the question can be simultaneously defined recursively, that is, whether there exists a common function $g$ for every value of $x_0$, or, equivalently, for every value of $n$.

Then the answer is negative.

To wit, for $n=4$, $x_0=\sqrt5$ and $x_1=\sqrt{1+4\sqrt6}$ while, for $n=2$, $x_1=\sqrt5$ and $x_2=\sqrt{1+2\sqrt{1+3\sqrt5}}$, thus, one would need that $$\sqrt{1+4\sqrt6}=g(\sqrt5)=\sqrt{1+2\sqrt{1+3\sqrt5}}$$ which is absurd.

| cite | improve this answer | |
  • $\begingroup$ "Amusing" revenge downvote, probably due to this character. $\endgroup$ – Did Nov 26 '18 at 23:09

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.